IMPLEMENTATION OF THE REHABILITATION PROGRAM FOR NARCOTICS INMATES AT THE CLASS IIB CORRECTIONAL INSTITUTION OF LUBUK PAKAM - Deskia Renata Br. Sitorus; Andry Syafrizal Tanjung; Rahmayanti (PT. Radja Intercontinental Publishing, 2025)
The narcotics problem in Indonesia continues to rise, with one-third of inmates convicted of drug offenses. This study analyzes the implementation and challenges of the rehabilitation program at the Class IIB Correctional Institution of Lubuk Pakam using a normative-empirical juridical approach. The program follows relevant regulations through WHO-ASSIST screening, assessment, staged rehabilitation, and post-rehabilitation. Cooperation with the Titian Harapan Indonesia Foundation has proven effective, with 85% of participants experiencing improved quality of life. Main obstacles include limited qualified personnel, infrastructure, coordination, and funding. Optimization requires capacity building, infrastructure improvement, partnership expansion, and increased financial support.